OoNAC72, a NAC-Type Oxytropis ochrocephala Transcription Factor, Conferring Enhanced Drought and Salt Stress Tolerance in Arabidopsis - Guan, Huirui; Liu, Xin; Niu, Fei; Zhao, Qianqian; Fan, Na; Cao, Duo; Meng, Dian; He, Wei; Guo, Bin; Wei, Yahui; Fu, Yanping (Frontiers in Plant Science, 2019)
The NAC proteins form one of the largest families of plant-specific transcription factors (TFs) and play essential roles in developmental processes and stress responses. In this study, we characterized a NAC domain transcription factor, OoNAC72, from a legume Oxytropis ochrocephala. OoNAC72 was proved to be localized in the nuclei in tobacco lower epidermal cells and had transcriptional activation activity in yeast, confirming its transcription activity. OoNAC72 expression could be induced by drought, salinity and exogenous abscisic acid (ABA) in O. ochrocephala seedlings. Furthermore, over-expression of OoNAC72 driven by CaMV35S promoter in Arabidopsis resulted in ABA hypersensitivity and enhanced tolerance to drought and salt stresses during seed germination and post-germinative growth periods. In addition, over-expression of OoNAC72 enhanced the expression of stress-responsive genes such as RD29A, RD29B, RD26, LEA14, ANACOR19, ZAT10, PP2CA and NCED3. These results highlight the important regulatory role of OoNAC72 in multiple abiotic stress tolerance, and may provide an underlying reason for the spread of O. ochrocephala.